Creating Customer Engangement and Customer Value within 15 second : How Tiktok Works for Content Marketing - Yana Respati Dewi (AMAR (Andalas Management Review), 2021)
Introduction/Main Objectives: This study iaims to analyze the effect of tiktok marketing-based content on customer engagement and customer value. Background Problems: Sosial media become major platform for marketing activities, and during pandemic covid on 2020 the social media used for marketing activities have shifted from Instagram to Tiktok. Therefore, this research explained how 15 second video can create customer engangement and customer value on product or services. Novelty: This research focused on customer engangement and customer value based on marketing content, but empirical studies of the context still limited or based on fan engangement (personal branding). Research Methods: This study was conducted using a quantitative analysis technique with path analysis method. The data obtained by distributing questionnaires online to 276 respondent which all of them are active users. Finding/Results: The result shows that video on tiktok with 15 second until 60 second duration has an impact for user. Different from existing media sosial platform, the effectiveness of using Tiktok requires accuracy and creativity of content. Interesting content does not necessarily attract consumers, but the content will provide product value or consumer attitudes towards the product. Conclusion: 90% of respondent agree that using Tiktok as marketing tools considered as an effective way. Especially when Tiktok become new-rising social media platform during the Pandemic 2020. Almost teens download the apps to join the trend, and until today, all the former infuencer on Instagram moves to Tiktok for creating the product ads content.